2015
DOI: 10.1016/j.aninu.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of xylanase on apparent ileal digestibility of nutrients, viscosity of digesta, and intestinal morphology of growing pigs fed corn and soybean meal based diet

Abstract: This study was to determine apparent ileal digestibility of acid detergent fiber (ADF), neutral detergent fiber (NDF), dry matter (DM), energy, organic matter (OM), crude ash, digesta viscosity, and gut morphology in nursery pigs fed diets containing xylanase (Lohmann Animal Nutrition GmbH, Cuxhaven, Germany). The diet (61% corn, 35% soybean meal, 1% poultry fat, and 3% minerals and vitamins) was mixed with 3 levels of xylanase (0, 700, and 1400 LXU/kg). Thirty-six barrows (17.6 ± 3.3 kg) received one of 3 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 53 publications
8
95
2
3
Order By: Relevance
“…Meanwhile, xylanase supplementation reduces the detrimental effects of arabinoxylans and increases digestibility of N and GE. The improvement in digestibility observed in this study was consistent with the results of Nian et al () and Passos et al (), who reported that the supplementation of xylanase in corn‐soybean meal based diet improved ileal digestibility of DM, organic matter, GE, neutral detergent fiber and crude ash. The improvement in ATTD of DM, N and GE with xylanase supplementation can, in turn, induce a significant increase in the ADG and G:F. These findings, combined with the improvement in growth performance with supplementation of 0.01% xylanase to corn‐soybean meal based diet in this study, suggested that the use of xylanase exerted a beneficial effect on weaning pig performance when a corn‐soybean meal based diet is used.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meanwhile, xylanase supplementation reduces the detrimental effects of arabinoxylans and increases digestibility of N and GE. The improvement in digestibility observed in this study was consistent with the results of Nian et al () and Passos et al (), who reported that the supplementation of xylanase in corn‐soybean meal based diet improved ileal digestibility of DM, organic matter, GE, neutral detergent fiber and crude ash. The improvement in ATTD of DM, N and GE with xylanase supplementation can, in turn, induce a significant increase in the ADG and G:F. These findings, combined with the improvement in growth performance with supplementation of 0.01% xylanase to corn‐soybean meal based diet in this study, suggested that the use of xylanase exerted a beneficial effect on weaning pig performance when a corn‐soybean meal based diet is used.…”
Section: Discussionsupporting
confidence: 92%
“…However, the results are not always consistent. Passos et al () reported that dietary supplementation of xylanase had no effect on ADG, ADFI or G:F in growing pigs fed a corn‐soybean meal based diet. Similar results were also reported in weaning and growing pigs fed wheat‐based diets (Mavromichalis et al ; Barrera et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean contains galactomannans which are associated with higher viscosity rate (Veum and Odle, 2001). The high intestinal viscosity of mannans has been previously shown to have negative effects on nutrient utilization (Passos et al, 2015). The lower ADG and F : G might be associated with lower digestibility of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The improved growth performance of growing pigs fed diet supplemented with β-mannanase found in these trials might be partly due to enhanced digestibility of DM, GE and β-mannan, which was in agreement with Kim et al (2013) who reported higher final BW, digestibility of DM and GE in β-mannanase supplemented diet. High levels of NSP in pig diets can cause an increase in digesta viscosity, preventing interaction between substrate and digestive enzymes and, hence, reducing the nutrient digestibility (O'Connell et al, 2005;Passos et al, 2015). Previous studies demonstrated that supplementation of exogenous enzymes to high-NSP diets reduced the viscosity of digesta and enhanced the nutrient utilization (Parkkonen et al, 1997;Grandhi, 2001;Ji et al, 2008;Tapingkae et al, 2008).…”
Section: Discussionmentioning
confidence: 99%